Association Analysis of Demographic Factors and the Likelihood of Self-reporting Mental Illness at Student Run Clinics - Malempati, Mahant; Patel, Jenilkumar; Gowda, Geetha R; Kazan, Osman; Pope, Helen (Journal of Student-Run Clinics, 2024)
Background: Patients in the student-run clinics operated by the Tulane University School of Medicine report higher rates of previous diagnoses of mental illness (45.3%) when compared to the national average (22.8%). The diverse group of patients who utilize these resources have various demographic factors that may influence the likelihood of reporting a mental illness. Our objective is to analyze data from Tulane University School of Medicine’s student-run clinics to identify associations of self-reported psychological diagnoses with demographic and psychosocial factors. Methods: Data collected from surveys filled out by students interviewing patients in student-run clinics (n=1494), chi-square analysis, and multivariate regression analysis were conducted to evaluate associations between self-reported psychiatric illness with demographic and psychosocial factors. Results: In the chi square analysis, patients who were age 18-39, reported using psychiatric medications, identified as White, were female, did not report being homeless, had a previous suicide attempt, had a history of trading drugs for sex or money, were a victim or witness of a violent or traumatic event, and had a history of physical, emotional, and sexual abuse were more likely to report a mental health condition. Patients aged 60-99, who were African American, male, reported homelessness were less likely to report a history of a mental health conditions. Persons who identified as male were the only category statistically associated with decreased odds of reporting a mental health diagnosis. In the regression analysis, patients aged 18-39, aged 40-59, who were female, white, who had a suicide attempt, and had a history of incarceration were likely to report a mental health diagnosis. Conclusions: Patients with specific demographic and psychosocial characteristics were more likely to report a mental health diagnosis.